2017
DOI: 10.2320/matertrans.m2016175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrodes and Post Weld Solution Annealing Treatment on Microstructures, Mechanical Properties and Corrosion Resistance of Dissimilar High Nitrogen Austenitic and Conventional Austenitic Stainless Steel Weldments

Abstract: In the present investigation, the dissimilar metal butt joints between low nickel high nitrogen 201 stainless steel and conventional 304 stainless steel were prepared by shielded metal arc welding process with two different llers, E308L and E309L. The effects of llers, along with variation in solution annealing temperature as 1050 C and 1100 C, on the microstructural characteristics, mechanical properties, and intergranular corrosion behaviour of dissimilar weldments were investigated. The primary δ-ferrites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The reason for the good microstructure uniformity and directivity of the weldments produced by the median value of 170 A and 200 A is that the heat input is stable in the stable welding process, which is conducive to the uniform growth of metal crystals. According to the crystal growth theory, the crystal growth direction is always along the direction of the maximum temperature gradient in the welding pool, so when the heat input of welding is stable, the weld microstructure shows good directivity [23,24]. The fracture characteristics of the weldments prepared by different backward median currents waveform remain consistent with the results of the mechanical properties tests, the fracture type of the weldments changes from ductile fracture of the base material to quasi-dissociative fracture.…”
Section: Stability Analysis Of Welding Processsupporting
confidence: 61%
“…The reason for the good microstructure uniformity and directivity of the weldments produced by the median value of 170 A and 200 A is that the heat input is stable in the stable welding process, which is conducive to the uniform growth of metal crystals. According to the crystal growth theory, the crystal growth direction is always along the direction of the maximum temperature gradient in the welding pool, so when the heat input of welding is stable, the weld microstructure shows good directivity [23,24]. The fracture characteristics of the weldments prepared by different backward median currents waveform remain consistent with the results of the mechanical properties tests, the fracture type of the weldments changes from ductile fracture of the base material to quasi-dissociative fracture.…”
Section: Stability Analysis Of Welding Processsupporting
confidence: 61%
“…% H2SO4). The improved corrosion resistance in diluted sulfuric acid solution was also recorded for post weld solution annealed austenitic stainless steel weldments by the authors [25]. As can be seen in figure 9 and figure 10, the previous sensitization was reflected in the appearance of the specimen cross-sections after long-term corrosion test.…”
Section: Resultsmentioning
confidence: 69%
“…This trend is prompting industries to employ dissimilar welds. In this context, a considerable amount of work has been carried out on the dissimilar welding of Cr-Ni ASSs and Cr-Mn-Ni-N ASSs [8,[10][11][12]. Himanshu et al [8] has examined the impact of welding processes and welding speed on the 304/201 ASS dissimilar welding.…”
Section: Introductionmentioning
confidence: 99%
“…The authors recommended that 304 ASS can be substituted by dissimilar welding with 201 ASS using gas tungsten arc welding (GTAW) at 2.0 and 2.7 mm/s welding speed. In another study, Himanshu et al [10] investigated the influence of post-weld heat treatment at temperatures of 1050 and 1100 • C on the shielded metal arc welded 304/201 ASS dissimilar joints. The authors reported that on increasing the post-weld treatment temperature, the tensile characteristics of weldments decreased, while the corrosion behavior of the weldments increased.…”
Section: Introductionmentioning
confidence: 99%